Study of histomorphological pattern of ovarian neoplastic and non-neoplastic lesions - Fatima, Rasheed; M., Sandhya; S., Sowmya T. (International Journal of Research in Medical Sciences, 2017)
Background: The ovary is a striking exception to the Virchow’s dictum that organs that are frequently the site of primary cancer are rarely involved in secondary malignancy, and vice versa. Both primary and secondary carcinomas of the ovary are relatively frequent and show an astounding variety of pathologic patterns. The objectives were to study the histomorphological diversity of various neoplasms and non neoplastic lesions of ovary. To provide a specific diagnosis based upon the histomorphological study which is of paramount clinical significance in further management of the patient. Methods: The present study is based on histomorphological evaluation of 100 cases of ovarian neoplastic and non neoplastic lesions received at the department of Pathology, tertiary care hospital from June 2008 to Aug 2010. Results: A wide variation of age was noted. Among neoplastic lesions, majority of the cases were seen in age group of 20-39 years i.e., 50.6%. Non neoplastic lesion occurred in all age group, but majority of the incidences were seen in the age group of 20 to 40 years of age, accounting for 60% of total occurrence. the commonest ovarian tumor was serous cyst adenoma constituting 54.1% (46 cases) of all ovarian neoplasm. Mucinous cyst adenoma was the second most common tumor. There were 72 cases (85%) of benign, 2 cases (2%) of borderline and 11 cases (13%) of malignant tumors in the present study. Conclusions: The diversity of neoplasms makes it mandatory to classify the tumors accurately by histopathological features following universally accepted classification.